The Impact of Social Media on the Purchase Intention of Organic Products. - Samaniego-Arias, M. (2025)
The main objective of this study was to assess whether social media directly influences purchase intention and how it indirectly influences key psychological determinants, such as environmental attitude, subjective norms, and perceived behavioral control, based on the Theory of Planned Behavior. A quantitative, cross-sectional, and correlational approach was adopted, with data collected through surveys of 430 people in Guayaquil, Ecuador, using a 5-point Likert scale. Reliability was tested using Cronbach’s alpha, while data analysis employed confirmatory factor analysis and structural equation modeling using SPSS 24 and AMOS 24. The results indicate that social media does not directly affect purchase intention but significantly influences environmental attitudes, subjective norms, and perceived behavioral control; consequently, these factors positively affect purchase intention. This study contributes to the literature by highlighting the indirect role of social media in shaping green purchasing behavior, suggesting that marketing strategies should focus on improving consumer attitudes, social support, and accessibility to organic products.